Student's Critical Thinking Skills in Solving Minimum Competency Assessment Problems on Social Arithmetics Topics - Rama Dina; Rooselyna Ekawati (MATHEdunesa, 2022)
The Minimum Competency Assessment is employed as a standard for student graduation since it is more innovative and pushes students to think critically, including social arithmetic problem that involves everyday life and the calculation of ratios and percentages. This study aims to identify students' abilities in solving social arithmetic problems with a critical thinking pattern. The subject of this study was a class of 8th graders who were given a basic mathematics test, and then from their test results, ten samples were taken to take the AKM test. The ten samples were taken from each category of predetermined values, with two students with the highest and lowest scores in each category. Additionally, the author conducted interviews to strengthen the author's data. The interview conducted is a semi-structured interview, where the author prepares questions about why errors occur in student work. Data analysis steps are collecting data, reducing it, presenting it, and drawing conclusions. The results of the study show that students are categorized into three levels, namely, low, medium, and high. The most frequently observed signs of critical thinking skills from these three categories are clarity and overview. While students rarely master focus and reason. The findings of this study can be used as a guide for developing instructional models and strategies for improving students' numeracy skills.Keywords: AKM, critical thinking skills, numerical skills, social arithmetics.